2010
DOI: 10.1016/j.cellimm.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ primes macrophages for inflammatory activation by high molecular weight hyaluronan

Abstract: The objective was to assess outcomes of IFNγ-priming upon macrophage activation by the synovial macromolecule high-molecular-weight hyaluronan [HMW-HA] in the context of rheumatoid arthritis inflammation. Human macrophages primed by IFNγ and activated by HMW-HA were evaluated for cytokine secretion by ELISA and Milliplex assay and activation profiles by nuclear transcription factor EIA. IFNγ-primed, HMW-HA-activated macrophages produced elevated levels of TNF and secreted the TH1 cytokine IL-12p70, while IFNγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
(34 reference statements)
0
20
0
1
Order By: Relevance
“…Upon analysis of specific macrophage subset marker expression under in vitro M1 (IFN-␥, LPS) and M2 (IL-4) conditions, we noticed some variations. 5 Fig. 4C and D).…”
Section: M1(f4/80mentioning
confidence: 88%
See 2 more Smart Citations
“…Upon analysis of specific macrophage subset marker expression under in vitro M1 (IFN-␥, LPS) and M2 (IL-4) conditions, we noticed some variations. 5 Fig. 4C and D).…”
Section: M1(f4/80mentioning
confidence: 88%
“…Stimulation of undifferentiated macrophages with lipopolysaccharide (LPS) and gamma interferon (IFN-␥), or tumor necrosis factor alpha (TNF-␣), induces polarization to the M1 phenotype (4,5). They can be recognized both in vitro and in vivo by the production of nitric oxide species (NOS), as well as other proinflammatory molecules, including TNF-␣, interleukin 1 (IL-1), IL-6, and CCL2 (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, resident tissue macrophages are long-lived and may naturally produce low levels of virus. HIV ϩ perivascular macrophages and macrophage-like microglia (39,40) in the brain have been associated with the emergence of antiretroviral drug resistance (41,42) and HIV-associated neurocognitive disorders (HAND) (43,44). HIV ϩ patients may also harbor viral populations in cerebrospinal fluid (CSF) that are genetically distinct from virus in the blood (45)(46)(47)(48)(49)(50) and that exhibit characteristics of macrophage/microglia tropism (51).…”
mentioning
confidence: 99%
“…HMW HA can reduce bleomycin-induced apoptosis in alveolar epithelial cells from wild type mice and the protective effect was not seen in TLR4 −/− mice (Jiang et al, 2005). Using TLR4-specific small interfering RNA (siRNA), the expressions of matrix metalloprotease 2 (MMP2) and IL-8 induced by HA were blocked (Wallet et al, 2010). Taylor et al (2007) also found that recognition of hyaluronan released in sterile injury involves a unique receptor complex dependent on TLR4, CD44, and MD-2.…”
Section: Discussionmentioning
confidence: 99%